PENGARUH KEBIJAKAN PERDAGANGAN LUAR NEGERI CHINA TERHADAP EKSPOR BRAZIL KE CHINA TAHUN 2013-2017 - Mindi Suci Pratiwi; Ahmad Jamaan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
China's foreign trade policy underwent dynamic changes over the last decades. The implementation of the policy in 2013-2017 was trade liberalization and openness with a focus on the multilateral trading system and industrial modernization based on China's socialist. The increasing of the bilateral relations between Brazil and China in the shape of strategic partnerships has an impact on the influence of China's policies for Brazil, especially in the shift of the orientation of Brazil's export commodities. The main aim of this research is to analyze the way trade policy of China change the orientation of Brazil export commodity in 2013-2017, which in the end cause export reprimarization. This study used tacsonomic research by using primary and secondary data through library research to collect the necessary information. Liberalism perspective, liberal trade theory and trade liberalization concept are applied for the theoretical framework, as nation states degree to analyze particular problem. The result of this study proved that in term of the quality, prize and technology, the Brazil manufactured products couldn’t compete in Chinese market, as the reason why Brazil only export primary product there. Beside that, Brazil’s tendency to shift into reprimarization of their export became the possibilities of Brazil dependant on China market and product.  Due to the influence of China policy, Brazil’s trade is significantly increasing and the trade volume such as export and import of both states are remarkably boosting up as the years to come. Keywords: export commodity, export reprimarization, foreign trade policy, strategic partnership, trade liberalization.